2008
DOI: 10.4049/jimmunol.181.10.7230
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Genetically Engineered to Express IL-10 Induce Long-Lasting Antigen-Specific Tolerance in Experimental Asthma

Abstract: ؉ mediastinal lymph node T cells from mice injected with OVA-IL-10-DCs protected OVA-sensitized recipients from airway eosinophilia upon OVA provocation. Our study describes a promising strategy to induce long-lasting Ag-specific tolerance in airway allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 51 publications
1
72
0
Order By: Relevance
“…Others have reported that IL-10 expression by IL-10-differentiated DCs is required to prevent development of the asthma phenotype in systemically sensitized mice (11) and that IL-10 expression by host cells, presumed to be regulatory T cells, is required for induction of tolerance in asthmatic mice that have been treated with IL-10-lentivirus-transfected DCs (14); the latter authors did not assess tolerization of AHR (14). In addition, we have reported that neutralization of IL-10 prevents DC10-induced regulatory T cells from suppressing effector T cell responses in vitro in our OVA-asthma system (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported that IL-10 expression by IL-10-differentiated DCs is required to prevent development of the asthma phenotype in systemically sensitized mice (11) and that IL-10 expression by host cells, presumed to be regulatory T cells, is required for induction of tolerance in asthmatic mice that have been treated with IL-10-lentivirus-transfected DCs (14); the latter authors did not assess tolerization of AHR (14). In addition, we have reported that neutralization of IL-10 prevents DC10-induced regulatory T cells from suppressing effector T cell responses in vitro in our OVA-asthma system (13).…”
Section: Discussionmentioning
confidence: 99%
“…We have further shown that DC10s induce T effector cells from asthmatic animals to alter their phenotype, adapting a bona fide regulatory T cell phenotype (13). Although DCs that are retrovirus transfected to express very high levels of IL-10 can induce a longlasting and robust tolerance (14), significant ethical issues would arise with using such cells clinically. The tolerance induced by regulatory DCs that are differentiated ex vivo with IL-10 is seemingly robust (7,11,13), but we have little information regarding the life span of that tolerance or its durability under allergen rechallenge conditions.…”
mentioning
confidence: 99%
“…The previous study demonstrated that the granulocyte colony stimulating factor (G-CSF) could promote the generation of regulatory DC in vitro; however, neutralization of IL-10 significantly inhibited this process, suggesting that IL-10 involved in regulatory DC generation (34). BMDC could translate into regulatory DC when genetically engineered to express IL-10, and induce longlasting antigen-specific tolerance with an experimental asthma model (35). Thus, the phenotype and cytokine secretion properties of DC-SOCS1 are similar to those of regulatory DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Lung CD11b lo CD103 + DC have also been shown to express a range of tight junction proteins, leading to the current concept that these cells can interact with bronchial epithelial cells and directly sample the lumen for inhaled allergens (23,24). Regulatory roles have also been described for lung pDC (25), and recent studies have also described populations of regulatory myeloid-origin DC that produce IL-10 and can limit Th2-mediated allergic airway responses (26)(27)(28).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%